2012
DOI: 10.1038/ijo.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids regulate adipokine production and the immune balance of omental adipose tissue in human obesity

Abstract: OBJECTIVES: (1) To investigate whether modulation of the cannabinoid type 1 receptor (CB1R) directly regulates the production of adiponectin (ApN) and other adipokines in omental adipose tissue (OAT) of obese subjects, (2) to establish in which cellular fraction of OAT the effects of CB1R blockade take place and (3) to unravel the underlying mechanisms. SUBJECTS AND METHODS: OAT was obtained from 30 obese subjects (body mass index: 40.6±1.3 kg m À 2 ) undergoing abdominal surgery. Primary cultures of explants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
3
24
1
Order By: Relevance
“…These results are consistent with in vitro results of Perwitz et al [28] and with the increase in adiponectin levels induced by the CBR1 antagonist rimonaband in humans, both in vitro [30] and in vivo [29]. Even though the effect of dronabinol might appear negligible, our finding raises the question whether the increased cannabinoid signalling -with higher doses and long-term treatment -may negatively affect insulin sensitivity in this group of patients.…”
Section: Leptin and Adiponectinsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with in vitro results of Perwitz et al [28] and with the increase in adiponectin levels induced by the CBR1 antagonist rimonaband in humans, both in vitro [30] and in vivo [29]. Even though the effect of dronabinol might appear negligible, our finding raises the question whether the increased cannabinoid signalling -with higher doses and long-term treatment -may negatively affect insulin sensitivity in this group of patients.…”
Section: Leptin and Adiponectinsupporting
confidence: 95%
“…Furthermore, adiponectin decreased during CBR1 receptor stimulation in vitro [28], while it increased during CBR1 antagonist stimulation in vitro as well as in vivo [29,30]. According to our current information, the effects of CBR1 stimulation on the endogenous adipokine secretion have not previously been documented in patients with AN.…”
Section: Introductioncontrasting
confidence: 60%
“…Thus, even though fat mass is increased in GPR55 -/-mice, due to the potential opposing effect of GPR55 deletion on inflammation, the inflammation profile of adipose tissues of GPR55 -/-mice remain unchanged. Ge et al showed that pharmacological blockers of endocannabinoids up-regulate adiponectin expression in visceral fat of obese subjects to elicit anti-inflammatory effects 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients, the CB1 receptor blocker rimonabant upregulated adiponectin mRNA expression in omental AT explants (Ge et al, 2013). Likewise, obese and diabetic patients treated with 20 mg rimonabant daily exhibited an increase in adiponectin levels (Després et al, 2005(Després et al, , 2009Rosenstock et al, 2008).…”
Section: Adiponectinmentioning
confidence: 97%